Religion in Motion Rethinking Religion, Knowledge and Discourse in a Globalizing World - Hensold, Julian; Kynes, Jordan; Öhlmann, Philipp; Rau, Vanessa; Schinagl, Rosa Coco; Taleb, Adela (Springer International Publishing : Imprint: Springer, 2020)
X, 255 p. 10 illus.